2015
DOI: 10.1002/mabi.201500314
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Polypeptoid Brushes

Abstract: Patterned polypeptoid brushes on gold and oxide substrates are synthesized by surface-initiated polymerization of N-substituted glycine N-carboxyanhydrides. Their biofouling resistance is shown by protein and cell adhesion experiments. The accessibility of the system to common patterning protocols is demonstrated by UV-lithography and a μCP approach. Moreover, the terminal secondary amine group of the polypeptoid brushes is functionalized with different fluorescent dyes to demonstrate their chemical accessibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 56 publications
(67 reference statements)
0
29
0
Order By: Relevance
“…This structural difference implies the absence of intermolecular hydrogen bonds which results in an enhanced thermal and solution processability with respect to most biopolymers. SAMs of polypeptoids and glycopeptoids have been reported to significantly reduce the attachment of non‐specific proteins, cells and bacteria …”
Section: Amphiphilic Polypeptides and Peptide‐mimic Polymersmentioning
confidence: 99%
“…This structural difference implies the absence of intermolecular hydrogen bonds which results in an enhanced thermal and solution processability with respect to most biopolymers. SAMs of polypeptoids and glycopeptoids have been reported to significantly reduce the attachment of non‐specific proteins, cells and bacteria …”
Section: Amphiphilic Polypeptides and Peptide‐mimic Polymersmentioning
confidence: 99%
“…46,47 We therefore base our study on peptoid brushes that have previously been shown experimentally to exhibit excellent antifouling properties. 18,[48][49][50][51][52] In particular, we simulate the behavior of a zwitterionic peptoid containing pairs of residues with oppositely charged sidechains interspaced between uncharged residues, which was previously shown to exhibit lower protein adsorption and E. coli attachment than an uncharged counterpart at low to intermediate grafting densities. 18 Special attention is paid to the balance between charge, hydration, and molecular volume and chain density effects.…”
Section: Introductionmentioning
confidence: 99%
“…This hybrid system combines the stealth‐like properties of polysarcosine with the multifunctionality of synthetic polypeptides . Polysarcosine has proven to be a highly protein‐resistant material, which is able to introduce stealth‐like properties to nano‐ or macroscopic surfaces, indicating to be an alternative to polyethylene glycol (PEG) . Polypept(o)ides are easily accessible by sequential nucleophilic ring opening polymerization (ROP) of α‐amino acid N ‐carboxyanhydrides (NCAs) and correspondingly of the N ‐substituted glycine N ‐carboxyanhydride (NNCA) .…”
Section: Introductionmentioning
confidence: 99%